A Study of the Possibility of a Science Associated with a Specific Worldview - Mostafa Taqavi (Journal of Philosophical Investigations, 2019)
There are two main sections in this paper. First, we will show that some of the chief 20th-century theories of science either have failed to demonstrate that value judgments do not influence the context of consolidation and determination of science or have accepted the role of value judgments in the context of consolidation and determination of science and theorized accordingly. For this purpose, the ideas of logical positivists, Willard Quine, Karl Popper, Thomas Kuhn, Imre Lakatos, Paul Feyerabend, and Roy Bhaskar on science are briefly reviewed. Finally, the validity of the following statement will be explored: if ‘science is influenced by cognitive-normative foundations of A’ then ‘the science based on cognitive-normative foundations of, say, B is possible.’ Subsequently, the following question will be contemplated: is pluralism in Cognitive-normative foundations accepted methodologically? In this way, the final section includes ratification of the possibility of science associated with a particular worldview and goes on to explain the issues important in the argument in favor of such science.